Dystrybucja filmów zagranicznych w Ludowej Republice Chorwacji na tle polityki kulturalnej Jugosławii (1944-1963) - Gluba, Justyna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The subject of this article is the distribution of foreign films in the People’s Republic of Croatia in 1944-1963 against the background of Yugoslavia’s cultural policy. The author considers as foreign films those that were not made in Yugoslavia or in the production or co-production of Yugoslav studios. The article aims to show in a cross-sectionally way the trends that led to the import of films into Yugoslavia from specific countries. These tendencies were shaped primarily by political factors, which are also pointed out in the article.